Immunological Changes in Pregnancy and Prospects of Therapeutic Pla-Xosomes in Adverse Pregnancy Outcomes - Devvanshi, Himadri; Kachhwaha, Rohit; Manhswita, Anima; Bhatnagar, Shinjini; Kshetrapal, Pallavi (Frontiers in Pharmacology, 2022)
Stringent balance of the immune system is a key regulatory factor in defining successful implantation, fetal development, and timely parturition. Interference in these primary regulatory mechanisms, either at adolescence or prenatal state led to adverse pregnancy outcomes. Fertility restoration with the help of injectable gonadotrophins/progesterone, ovulation-inducing drugs, immunomodulatory drugs (corticosteroids), and reproductive surgeries provides inadequate responses, which manifest its own side effects. The development of a potential diagnostic biomarker and an effectual treatment for adverse pregnancy outcomes is a prerequisite to maternal and child health. Parent cell originated bi-layered-intraluminal nano-vesicles (30–150 nm) also known as exosomes are detected in all types of bodily fluids like blood, saliva, breast milk, urine, etc. Exosomes being the most biological residual structures with the least cytotoxicity are loaded with cargo in the form of RNAs (miRNAs), proteins (cytokines), hormones (estrogen, progesterone, etc.), cDNAs, and metabolites making them chief molecules of cell-cell communication. Their keen involvement in the regulation of biological processes has portrayed them as the power shots of cues to understand the disease’s pathophysiology and progression. Recent studies have demonstrated the role of immunexosomes (immunomodulating exosomes) in maintaining unwavering immune homeostasis between the mother and developing fetus for a healthy pregnancy. Moreover, the concentration and size of the exosomes are extensively studied in adverse pregnancies like preeclampsia, gestational diabetes mellitus (GDM), and preterm premature rupture of membrane (pPROMs) as an early diagnostic marker, thus giving in-depth information about their pathophysiology. Exosomes have also been engineered physically as well as genetically to enhance their encapsulation efficiency and specificity in therapy for cancer and adverse pregnancies. Successful bench to bedside discoveries and interventions in cancer has motivated developmental biologists to investigate the role of immunexosomes and their active components. Our review summarizes the pre-clinical studies for the use of these power-shots as therapeutic agents. We envisage that these studies will pave the path for the use of immunexosomes in clinical settings for reproductive problems that arise due to immune perturbance in homeostasis either at adolescence or prenatal state.